Anti-crack ultra-strong high-flexibility emery carbon fiber tile adhesive and preparation method thereof
Through the composite of nano-silica modified carbon fiber with cement, sand, etc., and the bridging reaction of styrene-TM I copolymer, the problem of insufficient mechanical properties of existing carbon fiber tiles is solved, and the improvement of high flexibility and crack resistance is achieved.
Patent Information
- Application Number
- CN202411759939.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing carbon fiber ceramic tile glue has shortcomings in terms of mechanical properties and crack resistance, especially the flexural strength and compressive strength.
Nanosilicon dioxide modified carbon fiber is combined with cement, sand, cellulose ether and redispersible latex powder. The nanosilicon dioxide grafted carbon fiber is formed by reacting styrene-TM I copolymer with oxidized carbon fiber and nanosilicon dioxide surfaces to improve its dispersion and compatibility in ceramic tile glue.
The mechanical properties of ceramic tile adhesives are significantly improved, including tensile adhesive strength, compressive strength and flexural strength, improved crack resistance and flexibility, and maintained high performance in water immersion tests.
Smart Images

Figure BDA0005167660520000071 
Figure BDA0005167660520000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tile adhesives, and in particular to a crack-resistant, super-strong, high-flexibility diamond sand carbon fiber tile adhesive and a preparation method thereof. Background Art
[0002] The main components of tile adhesive are cement, sand, cellulose, redispersible latex powder, etc., which are mainly used in pasting ceramic tiles, facing tiles, floor tiles and other decorative materials. Improving the bonding performance and mechanical strength of tile adhesive has important applications. Carbon fiber is a functional inorganic fiber material with high strength, high modulus, and good high temperature resistance. It is widely used in adhesives, concrete and other building materials. The patent with publication number CN117417156A discloses a carbon fiber tile pasting material, tile adhesive and application. The obtained tile adhesive is made of cement, metakaolin, hollow glass microspheres, carbon fiber and other raw materials, and has the advantages of good bonding and good thermal conductivity. However, the patent did not improve the dispersibility of carbon fiber in tile adhesive, and the tile adhesive did not show good mechanical properties such as flexural strength and compressive strength. Summary of the invention
[0003] The technical problem solved by the invention is to provide a corundum carbon fiber tile adhesive with good mechanical properties and high flexibility.
[0004] The technical solution provided by the present invention is: a crack-resistant, super-strong and high-flexibility corundum carbon fiber tile adhesive, comprising 35-40 parts by weight of cement, 60-65 parts by weight of sand, 0.3-0.4 parts by weight of cellulose ether, 1-1.6 parts by weight of redispersible latex powder, 0.1-0.8 parts by weight of nano-silicon dioxide modified carbon fiber, and 1.5-4 parts by weight of corundum.
[0005] The preparation method of nano-silicon dioxide modified carbon fiber comprises the following steps:
[0006] Step (1), washing the carbon fiber with ethanol and water in turn, adding it to concentrated nitric acid for oxidation after drying, filtering it and washing it with water to obtain oxidized carbon fiber.
[0007] Step (2), adding oxidized carbon fiber to N,N-dimethylformamide, stirring, adding styrene-TM I copolymer and dibutyltin dilaurate, heating to 75-85° C. in a nitrogen atmosphere, stirring and reacting for 12-18 hours, then adding nano-silica, stirring and reacting for 24-36 hours, filtering, washing with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0008] Preferably, the sand is composed of medium sand and fine sand in a mass ratio of (34-42):(58-66); the particle size of the medium sand is 30-70 mesh, and the particle size of the fine sand is 70-150 mesh.
[0009] Preferably, in step (2), the mass ratio of oxidized carbon fiber, styrene-TM I copolymer, dibutyltin dilaurate, and nano-silicon dioxide is 100:(20-60):(0.5-1.8):(5-30).
[0010] Preferably, the average particle size of nano-silicon dioxide is 10-30 nm.
[0011] Preferably, the preparation method of the styrene-TM I copolymer is: add styrene, 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and dibenzoyl peroxide to toluene, add 75-80° C. in a nitrogen atmosphere, stir and react for 24-30 hours, pour the solution into methanol for precipitation after cooling, filter, and wash with methanol to obtain the styrene-TM I copolymer.
[0012] Preferably, the mass ratio of styrene, 3-isopropenyl-α,α-dimethylbenzyl isocyanate TM I, and dibenzoyl peroxide is 100:(2-8):(2.2-3).
[0013] Preferably, the preparation method of the crack-resistant, super-strong, and highly flexible diamond grit carbon fiber tile adhesive is as follows: water, cement, sand, cellulose ether, redispersible latex powder, nano-silicon dioxide-modified carbon fiber, and diamond grit are added to a mixer, stirred and mixed, and vibrated to degas, so as to obtain the crack-resistant, super-strong, and highly flexible diamond grit carbon fiber tile adhesive.
[0014] The technical effect of the present invention is as follows: the present invention uses silicate cement and sand as the matrix of tile adhesive, and mixes with nano-silicon dioxide modified carbon fiber, corundum, cellulose ether and redispersible latex powder to obtain crack-resistant super-strong high-flexibility diamond sand carbon fiber tile adhesive. The styrene-TM I copolymer containing isocyanate groups is used as a bridge connection to react with the hydroxyl groups on the surface of the oxidized carbon fiber and the hydroxyl groups on the surface of the nano-silicon dioxide in sequence, so that the nano-silicon dioxide is grafted on the surface of the carbon fiber. Since the compatibility between the nano-silicon dioxide and cement and sand is very good, the carbon fiber with the nano-silicon dioxide grafted on the surface is also very compatible with cement and sand, and can be evenly dispersed in the tile adhesive matrix, significantly improving the mechanical properties of the tile adhesive, showing very high tensile adhesive strength, compressive strength and flexural strength, which is beneficial to improving the crack resistance and flexibility of the tile adhesive. At the same time, the carbon fiber grafted polystyrene copolymer has certain hydrophobicity and mechanical properties, and is added to the tile adhesive matrix to improve water resistance and mechanical properties. The tile adhesive test piece still maintains a high tensile adhesive strength after being immersed in water for 7 days. DETAILED DESCRIPTION
[0015] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0016] The cement of the invention is P.O42.5 silicate cement; the particle size of medium sand is 30-70 meshes; the particle size of fine sand is 70-150 meshes; the specification of carbon fiber is 3mm; and the average particle size of corundum is 200 meshes.
[0017] Redispersible latex powder, Shandong Yade Waterproof Material Co., Ltd.
[0018] Example 1
[0019] (1) Wash the carbon fiber with ethanol and water in turn, weigh 1 g of the carbon fiber after drying, add it to 40 mL of 68% concentrated nitric acid, stir and oxidize for 6 h, filter and wash with water to obtain oxidized carbon fiber.
[0020] (2) Add 5 g of styrene, 0.2 g of 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and 0.12 g of dibenzoyl peroxide to 50 mL of toluene, heat to 80°C in a nitrogen atmosphere, stir and react for 24 hours, cool the solution, pour it into methanol for precipitation, filter it, and wash it with methanol to obtain a styrene-TMI copolymer.
[0021] (3) Add 1 g of oxidized carbon fiber to 80 mL of N,N-dimethylformamide, stir, then add 0.2 g of styrene-TMI copolymer and 5 mg of dibutyltin dilaurate, heat to 80 ° C in a nitrogen atmosphere, stir and react for 12 h, then add 0.05 g of nano-silica with an average particle size of 30 nm, stir and react for 24 h, filter, wash with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0022] (4) Add 2.5 kg of water, 3.8 kg of cement, 6.2 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 35:65), 36 g of cellulose ether, 0.14 kg of redispersible latex powder, 10 g of nano-silica modified carbon fiber, and 0.15 kg of corundum into the mixer, stir and mix, and vibrate to degas to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0023] Example 2
[0024] (1) Add 5 g of styrene, 0.1 g of 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and 0.11 g of dibenzoyl peroxide to 50 mL of toluene, heat to 80°C in a nitrogen atmosphere, stir and react for 24 hours, cool the solution, pour it into methanol for precipitation, filter it, and wash it with methanol to obtain a styrene-TM I copolymer.
[0025] (2) Add 1 g of oxidized carbon fiber (prepared in Example 1) to 100 mL of N,N-dimethylformamide, stir, add 0.5 g of styrene-TM I copolymer and 14 mg of dibutyltin dilaurate, heat to 85°C in a nitrogen atmosphere, stir and react for 12 h, then add 0.25 g of nano-silica with an average particle size of 10 nm, stir and react for 36 h, filter, wash with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0026] (3) Add 2.2 kg of water, 3.5 kg of cement, 6.5 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 40:60), 40 g of cellulose ether, 0.1 kg of redispersible latex powder, 30 g of nano-silica modified carbon fiber, and 0.22 kg of corundum into the mixer, stir and mix, and vibrate to degas, to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0027] Example 3
[0028] (1) Add 5 g of styrene, 0.4 g of 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and 0.15 g of dibenzoyl peroxide to 60 mL of toluene, add 75 °C in a nitrogen atmosphere, stir and react for 30 h, cool and pour the solution into methanol for precipitation, filter and wash with methanol to obtain a styrene-TM I copolymer.
[0029] (2) Add 1 g of oxidized carbon fiber (prepared in Example 1) to 100 mL of N,N-dimethylformamide, stir, add 0.4 g of styrene-TM I copolymer and 10 mg of dibutyltin dilaurate, heat to 85° C. in a nitrogen atmosphere, stir and react for 12 h, then add 0.18 g of nano-silica with an average particle size of 10 nm, stir and react for 24 h, filter, wash with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0030] (3) Add 3 kg of water, 4.0 kg of cement, 6.0 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 42:58), 40 g of cellulose ether, 0.1 kg of redispersible latex powder, 50 g of nano-silica modified carbon fiber, and 0.28 kg of corundum into the mixer, stir and mix well, and vibrate to degas, so as to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0031] Example 4
[0032] (1) Add 5 g of styrene, 0.3 g of 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and 0.14 g of dibenzoyl peroxide to 60 mL of toluene, heat to 80°C in a nitrogen atmosphere, stir and react for 24 hours, cool the solution, pour it into methanol for precipitation, filter it, and wash it with methanol to obtain a styrene-TM I copolymer.
[0033] (2) Add 1 g of oxidized carbon fiber (prepared in Example 1) to 100 mL of N,N-dimethylformamide, stir, add 0.3 g of styrene-TM I copolymer and 8 mg of dibutyltin dilaurate, heat to 75°C in a nitrogen atmosphere, stir and react for 18 h, then add 0.12 g of nano-silica with an average particle size of 10 nm, stir and react for 30 h, filter, wash with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0034] (3) Add 2.8 kg of water, 3.5 kg of cement, 6.5 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 34:66), 30 g of cellulose ether, 0.16 kg of redispersible latex powder, 65 g of nano-silica modified carbon fiber, and 0.34 kg of corundum into the mixer, stir and mix, and vibrate to degas, to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0035] Example 5
[0036] (1) Add 5 g of styrene, 0.4 g of 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and 0.15 g of dibenzoyl peroxide to 60 mL of toluene, heat to 80°C in a nitrogen atmosphere, and stir to react for 30 hours. After cooling, pour the solution into methanol for precipitation, filter, and wash with methanol to obtain a styrene-TM I copolymer.
[0037] (2) Add 1 g of oxidized carbon fiber (prepared in Example 1) to 100 mL of N,N-dimethylformamide, stir, add 0.6 g of styrene-TM I copolymer and 18 mg of dibutyltin dilaurate, heat to 75°C in a nitrogen atmosphere, stir and react for 18 h, then add 0.3 g of nano-silica with an average particle size of 10 nm, stir and react for 36 h, filter, wash with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
[0038] (3) Add 2.2 kg of water, 3.5 kg of cement, 6.5 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 40:60), 38 g of cellulose ether, 0.13 kg of redispersible latex powder, 80 g of nano-silica modified carbon fiber, and 0.4 kg of corundum into the mixer, stir and mix, and vibrate to degas, to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0039] Comparative Example 1
[0040] (1) Add 2.5 kg of water, 3.8 kg of cement, 6.2 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 35:65), 36 g of cellulose ether, 0.14 kg of redispersible latex powder, and 0.15 kg of corundum into a mixer, stir and mix, and vibrate to degas to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0041] Comparative Example 2
[0042] (1) Add 2.5 kg of water, 3.8 kg of cement, 6.2 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 35:65), 36 g of cellulose ether, 0.14 kg of redispersible latex powder, 10 g of oxidized carbon fiber, and 0.15 kg of corundum into a mixer, stir and mix, and vibrate to degas to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0043] Comparative Example 3
[0044] (1) Add 1 g of oxidized carbon fiber to 80 mL of N,N-dimethylformamide, stir, then add 0.2 g of styrene-TMI copolymer (prepared by Example 1) and 5 mg of dibutyltin dilaurate, heat to 80 ° C in a nitrogen atmosphere, stir and react for 12 h, filter, wash with N,N-dimethylformamide and water in turn to obtain modified carbon fiber.
[0045] (2) Add 2.5 kg of water, 3.8 kg of cement, 6.2 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 35:65), 36 g of cellulose ether, 0.14 kg of redispersible latex powder, 10 g of modified carbon fiber, and 0.15 kg of corundum into a mixer, stir and mix, and vibrate to degas, to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0046] Comparative Example 4
[0047] (1) Add 1 g of oxidized carbon fiber to 80 mL of N,N-dimethylformamide, stir, then add 0.05 g of nano-silica with an average particle size of 30 nm, stir, then filter to obtain nano-silica-carbon fiber.
[0048] (2) Add 2.5 kg of water, 3.8 kg of cement, 6.2 kg of sand (the sand is composed of medium sand and fine sand in a mass ratio of 35:65), 36 g of cellulose ether, 0.14 kg of redispersible latex powder, 10 g of nano-silica-carbon fiber, and 0.15 kg of corundum into a mixer, stir and mix, and vibrate to degas to obtain crack-resistant, super-strong, and highly flexible corundum carbon fiber tile adhesive.
[0049] According to the method of JC / T 547-2017, the tile adhesive specimens were formed and cured for 28 days, and the tensile adhesive strength M was tested. After curing the tile adhesive specimens for 21 days, they were soaked in water for 7 days, dried, and then the tensile adhesive strength M1 was tested.
[0050] The tile adhesive specimens were formed and cured according to the method of JC / T 1004-2017. The curing time was 28 days, and the compressive strength and flexural strength were tested. The test results are shown in Table 1.
[0051] Table 1: Test results
[0052]
[0053]
[0054] After testing, the crack-resistant super-strong high-flexibility diamond sand carbon fiber tile adhesive of Examples 1-5 has higher tensile adhesive strength, compressive strength and flexural strength. This is mainly because the styrene-TMI copolymer containing isocyanate groups is used as a bridge connection to react with the hydroxyl groups on the surface of the oxidized carbon fiber and the hydroxyl groups on the surface of the nano-silicon dioxide in turn, thereby grafting the nano-silicon dioxide on the surface of the carbon fiber. Since the compatibility between nano-silicon dioxide and cement (main component silicate) and sand (main component silica) is very good, the carbon fiber with nano-silicon dioxide grafted on the surface is also very compatible with cement and sand, and can be evenly dispersed in the tile adhesive matrix, significantly improving the mechanical properties of the tile adhesive, which is beneficial to improving the crack resistance and flexibility of the tile adhesive. At the same time, the carbon fiber grafted polystyrene copolymer has certain hydrophobicity and mechanical properties. Adding it to the tile adhesive matrix is beneficial to improving water resistance and mechanical properties. The tile adhesive specimen still maintains a high tensile adhesive strength after being soaked in water for 7 days.
[0055] Compared with Example 1, Comparative Example 1 did not add nano-silica modified carbon fiber, and the tensile adhesion strength, compressive strength and flexural strength of the tile adhesive specimen were lower.
[0056] Compared with Example 1, Comparative Example 2 adds oxidized carbon fiber, which has poor compatibility with cement and sand, poor dispersibility in the tile adhesive matrix, and poor carbon fiber reinforcement effect, resulting in low tensile adhesion strength, compressive strength and flexural strength of the tile adhesive specimens.
[0057] The modified carbon fiber in Comparative Example 3 is not grafted with nano-silica on its surface. In Comparative Example 4, the oxidized carbon fiber is physically blended with nano-silica, and nano-silica is not grafted on the carbon fiber surface. The dispersion of the carbon fiber in the tile adhesive matrix is poor, and the reinforcement effect is poor, resulting in low tensile adhesion strength, compressive strength and flexural strength of the tile adhesive specimens.
[0058] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive, characterized in that: The crack-resistant, super-strong, high-flexibility corundum carbon fiber tile adhesive comprises 35-40 parts by weight of cement, 60-65 parts by weight of sand, 0.3-0.4 parts by weight of cellulose ether, 1-1.6 parts by weight of redispersible latex powder, 0.1-0.8 parts by weight of nano-silicon dioxide modified carbon fiber, and 1.5-4 parts by weight of corundum; The preparation method of the nano-silicon dioxide modified carbon fiber comprises the following steps: Step (1), washing the carbon fiber with ethanol and water in turn, drying it, adding it to concentrated nitric acid for oxidation, filtering it, and then washing it with water to obtain oxidized carbon fiber; Step (2), adding oxidized carbon fiber to N,N-dimethylformamide, stirring, adding styrene-TMI copolymer and dibutyltin dilaurate, carrying out a primary reaction in a nitrogen atmosphere, then adding nano-silica, carrying out a secondary reaction, filtering, washing with N,N-dimethylformamide and water in turn, to obtain nano-silica modified carbon fiber.
2. The crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive according to claim 1, characterized in that: The sand is composed of medium sand and fine sand in a mass ratio of (34-42):(58-66); the particle size of the medium sand is 30-70 meshes, and the particle size of the fine sand is 70-150 meshes.
3. The crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive according to claim 1, characterized in that: In the step (2), the mass ratio of oxidized carbon fiber, styrene-TMI copolymer, dibutyltin dilaurate, and nano-silicon dioxide is 100:(20-60):(0.5-1.8):(5-30).
4. The crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive according to claim 1, characterized in that: The average particle size of the nano silicon dioxide is 10-30 nm.
5. The crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive according to claim 1, characterized in that: In step (2), the temperature of the primary reaction is 75-85°C, and the reaction time is 12-18 hours; the time of the secondary reaction is 24-36 hours.
6. The crack-resistant, super-strong, high-flexibility diamond sand carbon fiber tile adhesive according to claim 3, characterized in that: The preparation method of the styrene-TMI copolymer is as follows: styrene, 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and dibenzoyl peroxide are added to toluene, and the mixture is heated to 75-80° C. in a nitrogen atmosphere, and stirred for reaction for 24-30 hours. After cooling, the solution is poured into methanol for precipitation, filtered, and washed with methanol to obtain the styrene-TMI copolymer.
7. The crack-resistant, super-strong and highly flexible diamond sand carbon fiber tile adhesive according to claim 6, characterized in that: The mass ratio of styrene, 3-isopropenyl-α,α-dimethylbenzyl isocyanate TMI, and dibenzoyl peroxide is 100:(2-8):(2.2-3).
8. A method for preparing the crack-resistant, super-strong and highly flexible diamond grit carbon fiber tile adhesive as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: adding water, cement, sand, cellulose ether, redispersible latex powder, nano-silicon dioxide modified carbon fiber and corundum into a mixer, stirring and mixing, and vibrating to degas, so as to obtain crack-resistant, super-strong and highly flexible corundum carbon fiber tile adhesive.
9. Use of the crack-resistant, super-strong and highly flexible diamond grit carbon fiber tile adhesive as claimed in any one of claims 1 to 7 in tile products.
10. Use of the crack-resistant, super-strong and highly flexible corundum carbon fiber tile adhesive prepared by the preparation method as claimed in claim 8 in tile products.
Citation Information
Patent Citations
Carbon fiber ceramic tile pasting material, ceramic tile adhesive and application
CN117417156A
Carbon fiber modified nano green environment-friendly thin-film base material and preparation method thereof
CN106542776A
Dual-Cure Mechanism Polymeric Adhesives
US20240010888A1
Low temperature process for the preparation of isopropenyl-alpha, alpha-dimethylbenzyl isocyanate-grafted latexes
US5314964A